2016
DOI: 10.17921/2447-8938.2016v18n2p139-143
|View full text |Cite
|
Sign up to set email alerts
|

Panorama Geral Sobre Doenças Inflamatórias Intestinais: Imunidade e Suscetibilidade da Doença de Crohn e Colite Ulcerativa

Abstract: <p>Doenças Inflamatórias Intestinais (DII) são doenças autoimunes, caracterizadas por afecções sistêmicas inflamatórias crônicas, relacionadas principalmente ao trato gastrointestinal. São de cunho multifatorial, com prevalência e incidência variando de acordo com a genética, meio ambiente, microbiota intestinal e até mesmo um possível agente entérico infeccioso. Dentre as DII mais comuns, estão a Doença de Crohn e a Colite Ulcerativa, as quais possuem sintomas em comum, tais como dor abdominal, febre, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
2
3
0
5
Order By: Relevance
“…Studies show that although there is no distinction between genders for disease involvement, the higher occurrence among women may be due to hormonal factors, which may interfere with the expression of the disease, or else due to the progress in the technologies and methods for detecting the diseases and in the establishment of diagnoses, taking into account that women are more concerned about their health. 17,19 As for vitamin D, in the present study, most of the patients presented deficiency (63%), which agrees with the findings of Ulitsky et al 20 that, when evaluating 504 patients with IBD (403 with CD and 101 with CNUC), found vitamin D deficiency in 49.8% of the participants. Our data also combine with the findings of Levin et al, 21 who reported 38% of deficiency in a study with 78 participants.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Studies show that although there is no distinction between genders for disease involvement, the higher occurrence among women may be due to hormonal factors, which may interfere with the expression of the disease, or else due to the progress in the technologies and methods for detecting the diseases and in the establishment of diagnoses, taking into account that women are more concerned about their health. 17,19 As for vitamin D, in the present study, most of the patients presented deficiency (63%), which agrees with the findings of Ulitsky et al 20 that, when evaluating 504 patients with IBD (403 with CD and 101 with CNUC), found vitamin D deficiency in 49.8% of the participants. Our data also combine with the findings of Levin et al, 21 who reported 38% of deficiency in a study with 78 participants.…”
Section: Discussionsupporting
confidence: 92%
“…The results show that, among the evaluated patients, there was a prevalence of female gender, patients married or in a stable relation, with full elementary education, nonsmokers, with no family history of IBD, and with a higher occurrence of CD -findings that agree with the literature. [14][15][16][17] The data of the present study were similar to those found by Rosa, Silva Junior and Rosa 14 who, in a study with 48 patients in whom 66% were female, 66% were married, with a mean of 12.38 years of schooling, 85% non-smokers, and 81% with no family history of IBD. Our data also agree with those from Souza, Belasco, and Aguilar-Nascimento 18 that, among their 220 patients studied, 57% were women, 66% were married, with a mean of 9.17 years of schooling and 62% of non-smokers.…”
Section: Discussionsupporting
confidence: 86%
“…No entanto, países em desenvolvimento demonstram aumento do número de casos 22 . No Brasil, a prevalência da doença encontra-se na região Sul e Sudeste, e está relacionada a qualidade de vida, como padrão socioeconômico e saneamento básico, ocasionando uma modificação da microbiota intestinal 6,22,23 . Neste estudo observou um declínio no número de casos, sendo contrário aos achados da literatura.…”
Section: Discussionunclassified
“…Segundo Ferraz (2016), o acometimento transmural do trato gastrointestinal é a característica mais marcante da Doença de Crohn. As fístulas que se apresentam indicam que a inflamação penetrou órgãos ou os tecidos adjacentes e com a ativação do sistema imune, as proteases e metaloproteinases contribuem para a destruição dos tecidos.…”
Section: Doenças Infamatórias Intestinaisunclassified